Lichens growing on human bone remains: A case study from continental Patagonia (Deseado Massif, Santa Cruz, Argentina) - García, Renato Andrés; Magnin, Lucia Angelica; Miotti, Laura Lucia; Barrientos, Gustavo (Journal of King Saud University - Science)
Lichens are organisms capable of colonizing almost every type of materials, provided they are stable and have sufficient exposure to light. The growing of lichens on bone surface is rare, due to the speed to which this substrate is weathered and destroyed. For the most part, documented cases occur in extreme environments, such as the Arctic and Antarctic, where bone elements remain unaltered for long periods, although they have also been found in other latitudes. The aim of this paper is to describe the taxonomic diversity of the lichens growing on a set of human bones recovered at a looted Late Holocene aboriginal cairn burial (chenque) in southern continental Patagonia (Piedra Museo archaeological locality, Deseado Massif, Santa Cruz, Argentina). In the analyzed bone assemblage (NISP = 56), a total of 63 lichen thalli were recorded. They were assigned to seven different species, except one case that could only be determined at the genus level. This is the first well-described record of lichen flora growing on human bone remains for South America, having important implications for both archaeological and forensic sciences. Fil: García, Renato Andrés. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Avellaneda; Argentina Fil: Magnin, Lucia Angelica. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Arqueología; Argentina Fil: Miotti, Laura Lucia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Arqueología; Argentina Fil: Barrientos, Gustavo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Antropología; ...